India's Healthcare System and Government Health Schemes Amid the COVID-19 Crisis: A Comprehensive Analysis (ShodhVarta, 2024)
The Pradhan Mantri Atmanirbhar Swasth Bharat Yojana and Ayushman Bharat Yojana were launched during the COVID-19 pandemic to make the country self-reliant in the health sector. These schemes aim to develop a modern ecosystem for research and development, testing, and treatment within the country. Under the National Digital Health Mission, efforts are underway to create a robust digital infrastructure for the health system. Notable initiatives include promoting cleanliness habits, coordinating new and traditional healthcare practices, developing nutrition strategies and health infrastructure, ensuring the availability of generic medicines, and implementing schemes such as health insurance and health cards. Despite these efforts, the government faces significant challenges due to the vast nature of the healthcare system and the country's diverse socio-economic conditions. Nevertheless, the focus remains on the optimal use of resources by establishing strong partnerships and synergies among various health programs and stakeholders. Promoting innovation and modern technology for a quality, affordable, accessible, and effective national healthcare system is a positive step. The development of IT-based infrastructure and the creation of a favorable funding environment, supported by government initiatives, reflect progress toward achieving the goal of building a healthy and developed India by 2047.